Effect of Dentin Pretreatment with Arginine on Microshear Bond Strength of Etch-and-Rinse or Self-Etch Adhesive Systems - Borgo, Gabriela Oliveira; Vieira-Junior, Waldemir Francisco; Theobaldo, Jéssica Dias; Aguiar, Flávio Henrique Baggio; Lima, Débora Alves Nunes Leite (European Journal of Dentistry, 2019)
Objective The main purpose of this study was to evaluate the effect of dentin pretreatment with 8% arginine on the immediate and 6-month bond strength (BS) of adhesive systems and surface morphology of dentin.Materials and Methods Dentin bovine specimens (5 × 5 mm) were allocated into following pretreatments: without pretreatment (conventional technique, C) or exposure to arginine solution (A) for 5 minutes prior to tooth restoration. The adhesive procedure was performed using (n = 12): 3-step etch-and-rinse adhesive (Scotchbond Multipurpose—SBMP [C+SBMP and A+SBMP]); 2-step etch-and-rinse adhesive (Single Bond 2 - SB [C+SB and A+SB]); or 2-step self-etch adhesive (Clearfil SE Bond - CSEB [C+CSEB and A+CSEB]). After 24 hours, the composite resin restorations were evaluated immediately and after 6 months of water storage using a microshear test and fracture pattern. The dentin surface exposed to A was assessed by scanning electron microscopy (SEM). The immediate BS data were submitted to a two-way analysis of variance and Tukey's test, and the long-term BS results were analyzed using Kruskal–Wallis and Dunn tests (α = 0.05).Results There was a significant decrease in immediate and 6-month BS for the A+SB and A+CSEB groups, which differed statistically from the C group. The fracture pattern was predominantly adhesive for SB and CSEB adhesive for C and A. The SEM images presented a different conditioning pattern of the dentin exposed to A.Conclusion The dentin pretreatment with arginine interfered negatively in the immediate and long-term BS of the simplified adhesive system. However, the SBMP adhesive was not affected by arginine pretreatment presenting the most satisfactory results.
Keywords: arginine; dentin; adhesive systems; adhesion; dentin-bonding agents